ALLEVIATION OFPOVERTY IN INDIA: ROLE OF GOVERNMENTPOLICIES AND PROGRAMMES - Abdul Mohsin (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Poverty and Indian society are very much related when it comes to the aspect of diversification and complexities. Given India’s diversity and heterogeneity, inequality and poverty have been characteristic features of life in India for ages. The government of India after independence in 1947 followed a ’developmental policy based on interventionist central planning’ through the implementation of five-year plans and import substitution with the primary focus to reduce poverty among the masses and usher in an egalitarian society as per the ideals of its constitution. Political, economic setup saw a significant change in 1991 as it gradually adopted market-oriented economic policies. This period is often linked with liberalisation, privatisation and globalisation as its focus were less on state intervention and more on equitable distribution to make the borders of the Indian economy open to the outside world. The rapid expansion of the middle class in India with vast job opportunities, especially in the private sector, can be attributed to this ’LPG’ revolution of 1991. However, the post-1991 economic growth also led to more inequality of income, wealth and resources. The ample number of economically deprived section of people still form the majority of the strata of the Indian population.